EL PROXIMO SISMO.
ADEMAS CONTIENE: LOS OLVIDADOS DE HOLLYWOOD, P.[Sn] / VENEZUELA SEGUN CHAVEZ, P.2 / EL EXTRAÑO AMOR DE LAS LIBELULAS, P.24 / EL SIGUIENTE GRAN SISMO, P.40 / EL RECUENTO DEL TERROR, P.66 / GLEN SALE A LA LUZ, P.70 / DA MIEDO, ES CARA, PODRIA SALVAR A LA TIERRA, P.88 / LA LARGA SOMBRA DE CHERNOBYL, P.98